Linking perspectives: a field experiment on the role of multi-layer networks in refugee information sharing - Clark, Aaron Thomas; Larson, Jennifer M.; Lewis, Janet I. (Applied network science, 2024)
The social networks that interconnect groups of people are often “multi-layered”—comprised of a variety of relationships and interaction types. Although researchers increasingly acknowledge the presence of multiple layers and even measure them separately, little is known about whether and how different layers function differently. We conducted a field experiment in twelve villages in rural Uganda that measured real multi-layer social networks and then tracked their use in response to new, discussion-provoking information about refugees. We find that people who received our information treatment discussed refugees with more people, selected discussion partners from neighbors in the multi-layer network, and used most of the layers to do so. Treatment kicked off conversations throughout the villages that also included control respondents; treated and control both selected discussion partners from their networks who shared their attitudes towards refugees and were particularly interested in the subject. Our results point to multi-layer networks of day-to-day interactions as a source of prospective discussion partners when new information arises, especially layers based on shared meals, homestead visits, and money borrowing. When a relationship is based on multiple of these layers, it is even more likely to facilitate discussion. Furthermore, the selection of discussion partners from these networks depends less on any one particular layer and more on characteristics of the tie relative to the topic at hand.